Cdkn2a (Arf) loss drives NF1-associated atypical neurofibroma and malignant transformation. (15th May 2019) - Rhodes, Steven D; He, Yongzheng; Smith, Abbi; Jiang, Li; Lu, Qingbo; Mund, Julie; Li, Xiaohong; Bessler, Waylan; Qian, Shaomin; Dyer, William; Sandusky, George E; Horvai, Andrew E; et al.
Abstract: Plexiform neurofibroma (PN) tumors are a hallmark manifestation of neurofibromatosis type 1 (NF1) that arise in the Schwann cell (SC) lineage. NF1 is a common heritable cancer predisposition syndrome caused by germline mutations in the NF1 tumor suppressor, which encodes a GTPase-activating protein called neurofibromin that negatively regulates Ras proteins. Whereas most PN are clinically indolent, a subset progress to atypical neurofibromatous neoplasms of uncertain biologic potential (ANNUBP) and/or to malignant peripheral nerve sheath tumors (MPNSTs). In small clinical series, loss of 9p21.3, which includes the CDKN2A locus, has been associated with the genesis of ANNUBP. Here we show that the Cdkn2a alternate reading frame ( Arf ) serves as a gatekeeper tumor suppressor in mice that prevents PN progression by inducing senescence-mediated growth arrest in aberrantly proliferating Nf1 −/− SC. Conditional ablation of Nf1 and Arf in the neural crest-derived SC lineage allows escape from senescence, resulting in tumors that accurately phenocopy human ANNUBP and progress to MPNST with high penetrance. This animal model will serve as a platform to study the clonal development of ANNUBP and MPNST and to identify new therapies to treat existing tumors and to prevent disease progression.